2021
DOI: 10.3390/foods10092212
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Components and Preliminary Antibacterial Activity of Tamarillo (Solanum betaceum Cav.)

Abstract: Tamarillo is a nutrient-dense fruit with a unique aroma from its volatile compounds (VCs). In this study, we aimed to compare the volatile profiles: (i) of fresh and freeze-dried tamarillo; (ii) detected using Thermal Desorption–Gas Chromatography–Mass Spectrometry (TD–GC–MS) and Solid-Phase MicroExtraction–Gas Chromatography-Mass Spectrometry (SPME–GC–MS); (iii) of freeze-dried pulp and peel of New Zealand grown tamarillo. The possible antibacterial activity of freeze-dried tamarillo extracts was also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…These esters mainly originate from tamarillo [ 44 , 45 , 46 ] and can minimize the sharpness and bitterness imparted by fatty acids and amines in yoghurt [ 41 ]. The concentration of ethyl hexanoate in fortified yoghurts was significantly lower than the original amount present in tamarillo fruit [ 16 ]. This may have been due to the matrix effect of yoghurt, where proteins and exopolysaccharides, as well as physicochemical interactions between components like pectin and sucrose, affect the release of volatile compounds [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These esters mainly originate from tamarillo [ 44 , 45 , 46 ] and can minimize the sharpness and bitterness imparted by fatty acids and amines in yoghurt [ 41 ]. The concentration of ethyl hexanoate in fortified yoghurts was significantly lower than the original amount present in tamarillo fruit [ 16 ]. This may have been due to the matrix effect of yoghurt, where proteins and exopolysaccharides, as well as physicochemical interactions between components like pectin and sucrose, affect the release of volatile compounds [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 1–2 g yoghurt sample was quickly introduced into a 10 mL headspace vial. Ten μL of internal standard (6.5 mg/L solution of dichlorobenzene in water) was added to the vial and vortexed for 30 s. GC-MS coupled with SPME fibre was used for volatile analysis according to our previous study [ 16 ]. The total run time was 37 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers have examined the antibacterial activity of various other fruit peels such as tamarillo [60], bergamot (Citrus bergamia) [57,61], sweet lemon (C. limetta) [53,62], C. deliciosa [63], kumquat (C. japonica) [64] and feijoa (Acca sellowiana) [65]. Surprisingly, Diep et al [60] and Mandalari et al [61] revealed that the tamarillo and bergamot peel flavonoids, respectively, exhibited strong antibacterial activity against Gram-negative bacteria such as E. coli, Pseudomonas putida, S. enterica serovar Typhimurium and P. aeruginosa, while Gram-positive bacteria (B. subtilis, L. innocua, S. aureus) were resistant. Similarly, El-Hawary et al [63] found that C. deliciosa EO extracted from its leaves and peel was more effective against Gram-negative bacteria than the Gram-positive bacteria.…”
Section: Essential Oils From Other Fruit Peelsmentioning
confidence: 99%
“…Due to the difference in their cell wall structure [34], Gram-positive bacteria are more susceptible to EOs than Gram-negative bacteria [23,40,54,66]. However, published data have shown no clear differentiation between Gram-positive and Gram-negative bacteria [60,63]. The reason for this contradictory result is discussed in Section 4.…”
Section: Essential Oils From Other Fruit Peelsmentioning
confidence: 99%
“…Volatile components of the inoculated milk samples were analysed according to the methods used by the same research group [ 27 ] with slight modifications.…”
Section: Methodsmentioning
confidence: 99%